Comparison of Laparoscopy and Open Surgery for Women with Early Stage in low grade Endometrial Cancer - Joko Winarno; Chamim Chamim; Sarah Miriam Ratna Pratamasari (Syntax Corporation, 2023)
Endometrial cancer is a type of gynecological cancer that becomes a burden to the healthcare system. Laparotomy and laparoscopic surgical techniques are currently the two most common surgical methods for endometrial cancer. The laparoscopic approach was found to be associated with reduced operative morbidity. This study evaluated oncologic outcomes of laparoscopy and laparatomy surgery in the management in early stage of low-grade endometrial cancer. We conducted and observational study of woman diagnosed with International Federation of Gynecology and Obstetrics (FIGO-2018) early-stage endometrial cancer who underwent surgery at the Fatmawati Hospital, Jakarta, Indonesia from 2021-2022. The histopathological types are endometrial cell, well differentiated, no evidence invasion to the cervical/other organ (low grade). A total of 92 patients were treated for stage I endometrial cancer during the study period. Thirty-nine patients (42.4%) underwent laparoscopic surgery and 53 patients (57.6%) underwent laparotomy surgery. The average age of the laparoscopic group was younger than that of the laparotomy group. Comparison of laparotomy and laparoscopy in mean length of operation and amount of blood loss showed no statistically significant difference. The length of stay data showed mean length of stay in laparoscopic group was 3.67 days whereas in the laparotomy group was 5.14 days with significant result statistically. The mean survival of patients one year after the procedure is 49.49 weeks, with the average survival of 1 year in the laparoscopic group was 50.83 weeks and 47.98 weeks in laparotomy group with no statistically significant difference. Laparoscopic has view advantages especially, less blood loss, complication during operation, shorter hospital stay, 1 year survival rate but not significant statistically in this research.